The New Ephemeris and Light Curve Analysis of V870 Ara by the Ground-Based and TESS Data - Poro Atila (De Gruyter, 2021)
New CCD photometric observations and their investigation of the W UMa-type binary, V870 Ara, are presented. Light curves of the system were taken through BVIfilters from the Congarinni Observatory in Australia. The new ephemeris is calculated based on seven new determined minimum times, together with the TESS data and others compiled from the literature. Photometric solutions determined by the Wilson-Devinney (W-D) code are combined with the Monte Carlo simulation to determine the adjustable parameters’ uncertainties. These solutions suggest that V870 Ara is a contact binary system with a mass ratio of 0.082, a fillout factor of 96±4 percent, and an inclination of 73.60±0.64 degrees. The absolute parameters of V870 Ara were determined by combining the Gaia EDR3 parallax and photometric elements.